Hermeneutics Study: Analysis of Denotative And Connotative Meaning in The Song Berita Kepada Kawan By Ebiet G. Ade - Suryanti; Harto Malik; Zaedun Naim; Everhard Markiano Solissa; Zarkasi (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The song is a sequence of beautiful words, often carrying meanings both connotative (figurative) and denotative (literal). This research aims to unveil the connotative and denotative meanings in the song â€œBerita Kepada Kawanâ€ by Ebiet G. Ade. The theoretical framework employed in this study is hermeneutic research. It is a qualitative study where the data consists of sentences containing connotative and denotative meanings, and the source of the data is the lyrics of the song "Berita Kepada Kawan" by Ebiet G. Ade. Data were collected through free engagement observation. The researcher browsed the lyrics of the song â€œBerita Kepada Kawanâ€ by Ebiet G. Ade, then listened attentively to each word, phrase, sentence, and stanza of the lyrics. Subsequently, the researcher noted every sentence containing connotative and denotative meanings. Following this, data analysis was conducted, involving validation and classification of each sentence based on its type. The researcher then interpreted the data within its contextual framework. The results of the study indicate two meanings embedded in the song â€œBerita Kepada Kawanâ€, denotative and connotative. The denotative meaning portrays struggle, sadness, both mental and physical, while the connotative meaning depicts a solitary journey, sorrow, adversity, and loss of life. Thus, this hermeneutic research provides a profound understanding of the complexity of meanings in the song â€œBerita Kepada Kawan,â€ summarizing it within the conceptual framework of hermeneutics that includes both connotative and denotative analyses.